Intranasal versus intravenous midazolam in control of generalized tonic–clonic seizures in children - Kumar, M Veerendra; Sumi, K V (Indian Journal of Child Health, 2022)
Background: Seizures are very common in pediatric patients. As the duration of seizures impacts morbidity and mortality to child’s life, control of seizures should be achieved as early as possible, preferably at home. Intranasal (IN) midazolam is a simple method for control of seizures and can be administered by the parents. Objectives: To study the effectiveness of IN versus intravenous (IV) midazolam in control of generalized tonic–clonic seizures in children between 2 months and 12 years. Materials and Methods: We assessed the efficacy of IN midazolam in comparison with the same drug given by IV route. Neonates, children having partial seizures, and children who got prior medication for the present seizure and seizures that settled spontaneously were excluded from the study. 100 children were enrolled with 50 in each group. The two groups were analyzed for the time taken to control seizures from the time of drug administration. The number of treatment failures, recurrences, and treatment failure of recurrence were noted and compared. Results: The mean time for seizure control, treatment failures, number of recurrences, and treatment failure of recurrences were similar in both groups statistically. Conclusion: IN midazolam and IV midazolam are comparable in efficacy, however, IN midazolam is an easy route of drug delivery to control seizures.